PEMANFAATAN PIECES FRAMEWORK UNTUK ANALISA SISTEM INFORMASI RESERVASI DESTINASI WISATA DI KOTA PEKALONGAN - Much. Rifqi Maulana; Frisca Frishiliani Putri; Anas Syaifudin; Prastuti Sulistyorini (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2022)
The Tourism Destination Reservation Information System in Pekalongan City is an application that functions as a media for ordering tourist tickets online, managing tourist destination revenue results, displaying tourist locations, tourist details and the number of visitors to tourist destinations. Identification and evaluation of the system needs to be done to find out how satisfied users of the system. One method that can be used is the PIECES (Performance, Information and Data, Economics, Control and Security, Efficiency, and Service) Framework. Based on the results of the analysis that has been carried out by the Pieces Framework, it was found that the performance variable obtained a value of 2.30, information obtained a value of 2.47, economics obtained a value of 2.68, control obtained a value of 2.55, efficiency obtained a value of 2.46 and service obtained a value of 2.48. While the average number of each variable is 2.49 and is included in the VERY SATISFIED category. With these results it can be concluded that users are very satisfied with the Tourist Destination Reservation Information System in Pekalongan City. Keywords: Information System, tourist destination reservation, pieces framework